Glossary of Typesetting Terms. - Eckersley, Richard (Chicago guides to writing, editing, and publishing., 1994)
Glossary of Typesetting Terms is an up-to-date reference book on the craft of typography. It organizes a dictionary and a style guide into a single, one-stop resource. Prepared by a team of leading professionalsa designer, an editor, compositors, and production managersthis glossary will be valuable to anyone who works in publishing or printing for its definitions of typographical terms and concise treatment of typographical style. The glossary adds important details to discussions of typography that are covered more generally in editorial style guides such as The Chicago Manual of Style. It.